Effect of Case Management Interventions for Patients with Substance Use Disorders: A Systematic Review - Penzenstadler, Louise; Machado, Ariella; Thorens, Gabriel; Zullino, Daniele; Khazaal, Yasser (Frontiers in Psychiatry, 2017)
Background: Substance use disorder (SUD) is an important health problem that requires a complex range of care because of the chronic nature of the disorder and the multiple psychosocial problems involved. Current outpatient programs often have difficulties in delivering and coordinating ongoing care and access to different health care providers. Various case management (CM) models have been developed, first for patients in other psychiatric domains and then for patients with SUD, in order to improve treatment outcomes. Aims: This paper aims to assess the effectiveness of CM for patients with SUD. Methods: We performed a systematic review of CM interventions for patients with SUD by analyzing randomized controlled studies published on the subject between 1996 and 2016 found on the electronic database PubMed. Results and Conclusions: Fourteen studies were included in the analysis. Differences between studies in outcome measures, populations included, and intervention characteristics made it difficult to compare results. Most of these studies reported improvement in some of the chosen outcomes. Treatment adherence mostly improved, but substance use was reported to decrease in only a third of the studies. Overall functioning improved in about half of the studies. The heterogeneity of the results might be linked to these differences between studies. Further research is needed in the field.